Diagnostic Performance of Diffusion-weighted Magnetic Resonance Imaging in Bone Malignancy: Evidence From a Meta-Analysis. Issue 45 (November 2015) - Liu, Li-Peng; Cui, Long-Biao; Zhang, Xin-Xin; Cao, Jing; Chang, Ning; Tang, Xing; Qi, Shun; Zhang, Xiao-Liang; Yin, Hong; Zhang, Jian
Abstract : Abstract: Current state-of-the-art nuclear medicine imaging methods (such as PET/CT or bone scintigraphy) may have insufficient sensitivity for predicting bone tumor, and substantial exposure to ionizing radiation is associated with the risk of secondary cancer development. Diffusion-weighted MRI (DW-MRI) is radiation free and requires no intravenous contrast media, and hence is more suitable for population groups that are vulnerable to ionizing radiation and/or impaired renal functions. This meta-analysis was conducted to investigate whether whole-body DW-MRI is a viable means in differentiating bone malignancy. Medline and Embase databases were searched from their inception to May 2015 without language restriction for studies evaluating DW-MRI for detection of bone lesions. Methodological quality was assessed by the quality assessment of diagnostic studies (QUADAS-2) instrument. Sensitivities, specificities, diagnostic odds ratio (DOR), and areas under the curve (AUC) were used as measures of the diagnostic accuracy. We combined the effects by using the random-effects mode. Potential threshold effects and publication bias were investigated. We included data from 32 studies with 1507 patients. The pooled sensitivity, specificity, and AUC were 0.95 (95% CI, 0.90–0.97), 0.92 (95% CI, 0.88–0.95), and 0.98 on a per-patient basis, and they were 0.91 (95% CI, 0.87–0.94), 0.94 (95% CI, 0.90–0.96), and 0.97 on a per-lesion basis. In subgroup analysis, there is no statistical significance found in the sensitivity and specificity of using DWI only and DWI combined with other morphological or functional imaging sequence in both basis ( P > 0.05). A b value of 750 to 1000 s/mm 2 enables higher AUC and DOR for whole-body imaging purpose when compared with other values in both basis either ( P < 0.01). The ROC space did not show a curvilinear trend of points and a threshold effect was not observed. According to the Deek's plots, there was no publication bias on both basis. Our results support the use of DWI as an effective means for distinguishing malignant bone lesions; however, various imaging parameters need to be standardized prior to its broad use in clinical practice. Abstract : Supplemental Digital Content is available in the text